AMS assessment of U-contamination of structural materials of the Garigliano NPP under decommissioning. (July 2018) - Terrasi, F.; Buompane, R.; D'Onofrio, A.; Esposito, A.; Gialanella, L.; Marzaioli, F.; Petraglia, A.; Porzio, G.; Sabbarese, C.; Scolamacchia, F.; Sirignano, C.
Abstract: The assessment of the radiological impact of decommissioning activities at a Nuclear Power Plant requires a detailed mapping of the distribution of radionuclides both in the environment surrounding the NPP and in its structural material. The detection of long-lived actinide isotopes and possibly the identification of their origin is particularly interesting and valuable if ultrasensitive measurement of the relative abundance of U isotopes is performed via Accelerator Mass Spectrometry (AMS). In this paper we present an investigation carried out on the structural materials of the Garigliano NPP aiming to determine the abundance of 235, 236, 238 U in the various compartments of the plant buildings under decommissioning. Since the expected values both for isotopic ratios and total U concentrations range over different orders of magnitude, we have developed a novel methodology for the measurement of 234, 235 U/ 238 U isotopic ratios in low U concentration samples. This allowed a systematic investigation of the distribution of all U isotopes in concrete and metal matrices of the NPP. The behavior of 235, 236 U/ 238 U isotopic ratios in the different compartments of the NPP is discussed. The correlation of these ratios with 60 Co and 137 Cs specific activities is also studied to show a different behavior for concrete and metal samples. These data represent a very valuable information to direct the decommissioning procedures under course.